2015
DOI: 10.3301/ijg.2014.35
|View full text |Cite
|
Sign up to set email alerts
|

Bedding-parallel stylolites in shallow-water limestone successions of the Apulian Carbonate Platform (central-southern Italy)

Abstract: Bedding-parallel stylolites typically represent the product of chemical compaction (overburden weight-induced pressure solution) experienced by carbonate successions during their burial history, when bedding is still horizontal. Due to their common occurrence in carbonate rocks, with lateral extents that can exceed 1 km, beddingparallel stylolites are of special interest for the hydrocarbon industry because they may affect the regional fluid flow in the subsurface. Aimed at assessing the development and distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 72 publications
3
32
0
Order By: Relevance
“…Stylolites are planes of insoluble minerals that form in rocks as soluble minerals are removed by pressure solution (e.g., Park and Schot, 1968;Wanless, 1979;Nenna and Aydin, 2011;Croizé et al, 2013;Toussaint et al, 2018). They are common in limestones due to the relatively high solubility of calcite (e.g., Tondi et al, 2006;Fabricius and Borre, 2007;Benedicto and Schultz, 2010;Smith et al, 2011;Rustichelli et al, 2012;Agosta et al, 2012;Laronne Ben-Itzhak et al, 2014;Rustichelli et al, 2015;Martín-Martín et al, 2018), but are also found in sandstones (Heald, 1955;Walderhaug, 1996;Bjørkum et al, 1998;Walderhaug and Bjørkum, 2003;Emmanuel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stylolites are planes of insoluble minerals that form in rocks as soluble minerals are removed by pressure solution (e.g., Park and Schot, 1968;Wanless, 1979;Nenna and Aydin, 2011;Croizé et al, 2013;Toussaint et al, 2018). They are common in limestones due to the relatively high solubility of calcite (e.g., Tondi et al, 2006;Fabricius and Borre, 2007;Benedicto and Schultz, 2010;Smith et al, 2011;Rustichelli et al, 2012;Agosta et al, 2012;Laronne Ben-Itzhak et al, 2014;Rustichelli et al, 2015;Martín-Martín et al, 2018), but are also found in sandstones (Heald, 1955;Walderhaug, 1996;Bjørkum et al, 1998;Walderhaug and Bjørkum, 2003;Emmanuel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their macroscopically planar form, the influence of stylolites on fluid flow and reservoir compartmentalisation has drawn considerable interest. A handful of experimental studies have shown that stylolites can provide conduits for flow (Lind et al, 1994;Mallon and Swarbrick, 1998;Heap et al, 2014;Rustichelli et al, 2015), challenging paradigms that stylolites present barriers to fluid flow (Dunnington, 1967;Nelson, 1981;Burgess and Peter, 1985;Koepnick, 1987;Finkel and Wilkinson, 1990;Dutton and Willis, 1998;Alsharhan and Sadd, 2000). Heap et al (2014), for example, measured the permeability of limestone samples that contained no stylolites, one stylolite perpendicular to the imposed fluid flow, or one stylolite parallel to flow.…”
Section: Introductionmentioning
confidence: 99%
“…Rustichelli et al. () documented the abundance of bedding‐parallel stylolites and pseudo‐bedding in Cretaceous limestone in the southern Appennines. These rocks crop out abundantly on the Gargano Promontory and the Murge Plateau, both bordering the Adriatic Sea.…”
Section: Discussionmentioning
confidence: 99%
“…At Monte Sant'Angelo Castle on the Murge Plateau, the Giant's Tower (Torre dei Giganti, constructed in 837) may be a candidate for the pseudo‐bedded limestone described by Rustichelli et al. ().…”
Section: Discussionmentioning
confidence: 99%
“…As bedding-parallel stylolites and stratabound joints and veins typically form during burial (Fig. 14;Bathurst, 1995;Agosta et al, 2009;Rustichelli et al, 2012Rustichelli et al, , 2015bRustichelli et al, , 2016, remnants of such features indicate that the limestones had a significant overburden at the time of dolomitization (at least 90 to 300 m; e.g. Tada & Siever, 1989;Ebner et al, 2009).…”
Section: Depth and Age Of Dolomitizationmentioning
confidence: 99%